Lysyl oxidase-like 4 exerts an atypical role in breast cancer progression that is dependent on the enzymatic activity that targets the cell-surface annexin A2 - Komalasari, Ni Luh Gede Yoni; Tomonobu, Nahoko; Kinoshita, Rie; Chen, Youyi; Sakaguchi, Yoshihiko; Gohara, Yuma; Jiang, Fan; Yamamoto, Ken-ich; Murata, Hitoshi; Ruma, I Made Winarsa; Sumardika, I Wayan; Zhou, Jin; et al. (Frontiers in Oncology, 2023)
Background: LOX family members are reported to play pivotal roles in cancer. Unlike their enzymatic activities in collagen cross-linking, their precise cancer functions are unclear. We revealed that LOXL4 is highly upregulated in breast cancer cells, and we thus sought to define an unidentified role of LOXL4 in breast cancer. Methods: We established the MDA-MB-231 sublines MDA-MB-231-LOXL4 mutCA and -LOXL4 KO, which stably overexpress mutant LOXL4 that loses its catalytic activity and genetically ablates the intrinsic LOXL4 gene, respectively. In vitro and in vivo evaluations of these cells' activities of cancer outgrowth were conducted by cell-based assays in cultures and an orthotopic xenograft model, respectively. The new target (s) of LOXL4 were explored by the MS/MS analytic approach. Results: Our in vitro results revealed that both the overexpression of mutCA and the KO of LOXL4 in cells resulted in a marked reduction of cell growth and invasion. Interestingly, the lowered cellular activities observed in the engineered cells were also reflected in the mouse model. We identified a novel binding partner of LOXL4, i.e., annexin A2. LOXL4 catalyzes cell surface annexin A2 to achieve a cross-linked multimerization of annexin A2, which in turn prevents the internalization of integrin β-1, resulting in the locking of integrin β-1 on the cell surface. These events enhance the promotion of cancer cell outgrowth. Conclusions: LOXL4 has a new role in breast cancer progression that occurs via an interaction with annexin A2 and integrin β-1 on the cell surface.